Den friska boken och den sjuka läsaren - Magnus Persson (Educare)
Central agents of the institution of literature (critics, authors, scholars) find it increasingly hard to explain why reading literature is important. This leaves the field open for other interests to legitimize what was once a core value in education and the wider public sphere. One example of this is the increased interest in the potential health effects of producing and consuming culture, including the reading and writing of literature. This article targets the phenomenon of bibliotherapy, i.e. a field and practice concerned with how literature can function as a kind of medicine, thus making the reader healthier, more harmonious etc. Three examples are scrutinized: a popular introduction to bibliotherapy from the early 60s, an anthology from 2004 with a wide range of contributors, from researchers to psychiatrists, and, finally, a “therapeutic diary” from 2010 by the famous Swedish pop singer Caroline af Ugglas and the poet and psychoanalyst Ulf Karl Olov Nilsson. What conceptions of literature and reading can be discerned in these texts? Which values and ideologies lie beneath the renewed interest in literature as a kind of medicine?